The Role of Dramatic Works in I.S Turgenev’s Creating’s (Eurasian Journal of Humanities and Social Sciences, 2023)
This article discusses the interest in the study of the dramatic heritage of I.S. Turgenev, the role of the writer's drama in Russian literature and famous dramatic works of Turgenev.